Re-defining the role of surgery in the management of patients with oligometastatic stage IV melanoma in the era of effective systemic therapies. (August 2021) - Ch'ng, Sydney; Uyulmaz, Semra; Carlino, Matteo S.; Pennington, Thomas E.; Shannon, Kerwin F.; Rtshiladze, Michael; Stretch, Jonathan R.; Nieweg, Omgo E.; Varey, Alexander H.R.; Hsiao, Edward; Kapoor, Rony; Pires da Silva, Ines; et al.
Abstract: Although previously the mainstay of treatment, the role of surgery in the management of patients with oligometastatic stage IV melanoma has changed with the advent of effective systemic therapies (most notably immunotherapy). Contemporary treatment options for patients with asymptomatic solitary or oligo-metastases include upfront surgery followed by adjuvant immunotherapy or upfront immunotherapy with salvage surgery as required. For suspected solitary or oligo-metastases, surgery serves both diagnostic and therapeutic purposes. Advances in radiological technology allow metastases to be detected earlier and surgery to be less morbid. Surgical morbidities are generally more tolerable than serious immune-related adverse effects, but surgery may be less effective. Upfront immunotherapy ensures that futile surgery is not offered for rapidly progressive disease. It also provides an opportunity to assess response to treatment, which predicts outcome, and may obviate the need for surgery. However, it is important not to miss a window of opportunity for surgical intervention, whereby if disease progresses on immunotherapy it becomes unresectable. In situations where local therapy is recommended but surgery is not desired, stereotactic radiosurgery may be an effective alternative. The decision-making process regarding upfront surgery versus immunotherapy needs to take place within a specialist melanoma multidisciplinary setting and be customised to individual patient and tumour factors. Ultimately, high-level clinical trial evidence is required to resolve uncertainties in the management of patients with oligometastatic stage IV melanoma but the complexity of the varying presentations may make trial design challenging. Highlights: The role of surgery for asymptomatic oligometastatic stage IV melanoma has changed. Patient/tumour factors impact on decision-making (upfront surgery vs immunotherapy). Discussion at specialist melanoma multidisciplinary meetings is recommended. Prospective randomised trial evidence is required to resolve uncertainties.